1997
DOI: 10.1177/095632029700800306
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic Phosphonomethylether Nucleoside Inhibitors of Respiratory Viruses

Abstract: SummaryA series of acyclic phosphonomethylether nucleosides were synthesized and then evaluated for inhibitory activity against respiratory viruses of clinical significance using CPE inhibition, neutral red uptake and virus yield reduction assays. Of the 20 compounds synthesized, none significantly inhibited influenza A or B viruses or respiratory syncytial virus strains A2, Long or 18537; the selective indices (51) were less than 10. A new compound, G5-2128 (2R, 5R-9-[2,5-dihydro-5-(phosphonomethoxy)-2-furany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…To determine the effect of the guanosine analogue ribavirin on production of infectious EBOV in vitro, eGFP-ZEBOV was grown at a low MOI in Vero E6 cells with media containing a range of concentrations of ribavirin. Consistent with other published reports, ribavirin-induced cytotoxicity was not observed at the concentrations used (18,35,36). Viral titers of the supernatants revealed that increasing concentrations of ribavirin resulted in decreasing quantities of infectious virus (Fig.…”
Section: Effect Of Guanosine Analogue On Ebola Virus Mutation Frequensupporting
confidence: 80%
“…To determine the effect of the guanosine analogue ribavirin on production of infectious EBOV in vitro, eGFP-ZEBOV was grown at a low MOI in Vero E6 cells with media containing a range of concentrations of ribavirin. Consistent with other published reports, ribavirin-induced cytotoxicity was not observed at the concentrations used (18,35,36). Viral titers of the supernatants revealed that increasing concentrations of ribavirin resulted in decreasing quantities of infectious virus (Fig.…”
Section: Effect Of Guanosine Analogue On Ebola Virus Mutation Frequensupporting
confidence: 80%
“…A neutral red assay of the same plate was done to verify the results from the CPE assay spectrophotometrically (see below). The usual correlation between the two assays has been greater than 95% (Barnard, 1997a).…”
Section: Cytopathic Effect Inhibition Assaymentioning
confidence: 99%
“…was added to each well in a small volume. At '0' time, the virus were added within 5 min of drug addition as described previously for the CPE inhibition assay (Barnard et al, 1997a from visual and NR assays as described above.…”
Section: Cytopathic Effect Inhibition Timing Assaymentioning
confidence: 99%
See 2 more Smart Citations